Does non-operative treatment of appendicitis can replace surgery? - literature overview - Mika, Dawid; Turek, Kamila; Greguła, Anna; Kłos, Aleksandra; Mazur, Bartosz; Stachyrak, Karol; Mazurek, Aleksandra; Pawlicki, Mateusz; Wilanowska, Wiktoria; Lambach, Maciej (Journal of Education, Health and Sport, 2024)
Introduction and purpose Acute appendicitis, a common surgical abdominal ailment, mostly affects individuals in their second or third decade of life, with an annual incidence of about 100 cases per 100,000 persons. This literature review aims to synthesize evidence from diverse sources, summarizing optimal practices for clinical implementation. Surgical intervention, achieving almost 100% cure rates, remains the gold standard, emphasizing challenges in patient qualification for non-surgical approachesNon-operative treatment, considered safe for uncomplicated cases, involves antibiotic therapy, with concerns about antibiotic resistance. Summarizing the current understanding of antibiotic therapy of appendicitis seeks to enhance its effective use, decrease adverse incidents in patients, and contribute to the overall safety of both patients and healthcare providers. Material and methods The following review of studies was based on articles obtained from the PubMed and Google Scholar databases. Key search terms included acute appendicitis, acute appendicitis conservative treatment, appendectomy, surgical abdominal diaseases, antibiothic therapy. Conclusions The literature review highlights the existing challenges in the management of acute appendicitis, acknowledging the efficacy of both methods. While surgical intervention with high cure rates, the increasing popularity of non-operative therapy encourages optimism for comprehensive research in the future. The need for large, randomized studies comparing long-term clinical effectiveness is emphasized, aiming to inform decision-making and optimize patient outcomes.